Organizational Commitment Viewed from Managerâ€™s Transformational Leadership Style - Fatwa Tentama (HUMANITAS: Indonesian Psychological Journal, 2014)
ABSTRACTThe research aims at testing empirically the influence of managerâ€™s transformational leadershipÂ style on organizational commitment. The proposed hypthesis is positive relationship between managerâ€™sÂ transformational leadership style and organizational commitment.The subjects of the research areÂ 40 employees of Batik Company â€œNyonya Indoâ€. The subjects used in the research should meet theÂ requirements, i.e.: 1). Men and women, 2). Permanent employee, 3). Have been working at leastÂ for a year. Transformational leadership style and organizational commitment scales were used toÂ collect the data. The method of data analysis used is product moment correlation of PearsonÂ through SPSS program of 17.00 for windows version. The result shows that there is significantÂ positive correlation between managerâ€™s transformational leadership style and organizationalÂ commitment. This is depicted in r = 0,297 and p < 0,05. It means that the higher the transformationalÂ leadership style is applied, the higher the organizational commitment and vice versa. The number ofÂ the influence of managerâ€™s transformational leadership style on organizational commitmentis 7,841Â %.Keywords: organizational commitment, transformational leadership style,